Matthew Arnold: Pessimist?. Issue 4 (19th May 2021) - O'Gorman, Francis
ABSTRACT: This essay proposes both an empirical argument and a (speculative) conceptual one. The empirical argument concerns the question: did the original readers of Matthew Arnold's poetry anticipate later twentieth-century views that he was a Schopenhauer-like pessimist and representative of a deep seam of such thinking in the nineteenth century? The essay can find little evidence for this but rather for an Arnold whose periodical departures into mélancolie were assessed as aesthetic errors amid writing that was otherwise viewed to be charming. The essay notes how frequently poems that would seem exemplary of the age to later critics are either only briefly mentioned, not mentioned at all, or made the subject of near-parodic commentary by the original reviewers. The last portion of the essay reflects on the implications—acute for the body of work examined here—of a major difference between original readers' views and subsequent ones and asks an Arnoldian question of Arnold about what the object of criticism in such cases really is—or could be.